Por uma escola formadora: da pedagogia da concorrência à pedagogia da ação comunicativa - Binsfeld, André (2024)
The dream of a school that makes students citizens of the world, aiming to build a truly participatory democracy, was the driving force behind this research. After So many years of teaching and school management by the author, this dream seemed like an unfair fight between democratic necessity and utilitarian reality. This dichotomy boosted studies aiming at ways out of the impulses of the liberal system , through an education that rescues the human liberation, hostage to the economic and political interests of such a system. The initial problem of what to research then arose: The school must prepare for humanization or merely preparing for work in view of consumption? Throughout the readings, there was a need to reformulate the problem in a more objective way, as preparation for work is a fundamental condition. We moved on to a new question: Why choose a technical school that teaches competition and not a school formative for dialogical socialization? This way, the objective can be defined: to understand the elements of the technical competitive choice in order to present arguments that present viable proposals to demonstrate that the best choice would be a liberating and criticism. We started, firstly, with the history of Brazilian education, trying to understand which motivated decisions for a school in the format we know it today. When viewing Therefore, contradictions were noticed between the liberation discourses and the coercive practices of the liberal model that organizes technical and instrumentalizing pedagogy, focused on activity economic.